Microneedle-array patches loaded with dual mineralized protein/peptide particles for type 2 diabetes therapy. Issue 1 (December 2017) - Chen, Wei; Tian, Rui; Xu, Can; Yung, Bryant; Wang, Guohao; Liu, Yijing; Ni, Qianqian; Zhang, Fuwu; Zhou, Zijian; Wang, Jingjing; Niu, Gang; Ma, Ying; et al.
Abstract The delivery of therapeutic peptides for diabetes therapy is compromised by short half-lives of drugs with the consequent need for multiple daily injections that reduce patient compliance and increase treatment cost. In this study, we demonstrate a smart exendin-4 (Ex4) delivery device based on microneedle (MN)-array patches integrated with dual mineralized particles separately containing Ex4 and glucose oxidase (GOx). The dual mineralized particle-based system can specifically release Ex4 while immobilizing GOx as a result of the differential response to the microenvironment induced by biological stimuli. In this manner, the system enables glucose-responsive and closed-loop release to significantly improve Ex4 therapeutic performance. Moreover, integration of mineralized particles can enhance the mechanical strength of alginate-based MN by crosslinking to facilitate skin penetration, thus supporting painless and non-invasive transdermal administration. We believe this smart glucose-responsive Ex4 delivery holds great promise for type 2 diabetes therapy by providing safe, long-term, and on-demand Ex4 therapy. Diabetes treatments often rely on frequent and scheduled drug administration, which reduces patient compliance and increases treatment cost. Here, the authors develop a microneedle-array patch that separately loads drug-releasing module and glucose-sensing element for on-demand, long-term diabetes therapy.